Estudo das condições gerais da barragem Armando Ribeiro Gonçalves - Santos, Douglas Rodrigues dos (Universidade Federal Rural do Semi-Árido, 2020)
Since ancient times, human beings seek form for the accumulation of water. Dams are constructions used by civilizations for a long time, with the objective of accumulating water for agriculture, fishing, supplying the population. Brazil, for being the country that has the largest freshwater reserve in the world, has a large number of dams. Those dams, although bringing vast benefits, bring with them a high risk potential in the event of a collapse, causing catastrophic consequences for both the environment and human life. The state of Rio Grande do Norte has 619 reservoirs cataloged by the National Water Agency (ANA), 515 of which underwent an inspection in 2018, with five of them presenting problems; however, many of the small reservoirs are not cataloged. Large and small reservoirs are of paramount importance to combat the water scarcity that plagues the state. Thus, the present work aims to carry out a survey of the general conditions of the Armando Ribeiro Gonçalves Dam, located between the municipalities of São Rafael-RN, Assú-RN and Itajá-RN. To this end, a study was prepared containing the constructive history of the dam throughout its useful life and visits were made in loco to identify possible anomalies present in the dam. The main anomalies observed in the downstream and upstream embankments and in the dam crest were: damaged asphaltic mesh, holes in the asphalt mesh, presence of animals, presence of vegetation and small and medium-sized trees on the embankments, obstructed drainage channels.
Monografia
Keywords: Barragem; Anomalias; Reservatórios; Dam; Anomalies; Reservoirs; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA